Prospective Visual Arts Teachers’ Innovation Skills and Attitudes towards Computer Assisted Instruction - Kara, Sema (ISTES Organization, 2020)
The aim of this study is to examine the prospective visual arts teachers' innovation skills and their attitudes towards computer-assisted teaching in terms of demographic and school factors. In this context, using comparative relational research model; the students' attitudes towards innovation skills and computer assisted teaching were examined with a comparative approach. The study group of this research consists of 305 visual arts teacher candidates studying at Dicle University, Anadolu University, Mersin University, Necmettin Erbakan University and Marmara University. Attitude scale and innovation skills scales were used to collect data. According to the analysis of the data, it was seen that visual arts teacher candidates' perceptions of innovation skills and their attitudes towards computer aided teaching are high. In addition, significant differences were found in computer aided teaching attitudes and innovation skills according to faculty type, grade level and gender. Finally, significant relationships were found between innovation skills and entrepreneurship perception.
Keywords: 4. Education